The Role of Content Marketing Implementation at Social Media Instagram @arswama.media - Deandra Hudry Rusfan; Donni Junipriansa (PT. Publikasiku Academic Solution, 2024)
Arsana Swastika Prima or with the trademark Arswama Media is a company engaged in inde publishing and printing, in the midst of the unsteady publishing and printing business Arswama Media still maintains its business to help inde writers. So far, Arswama Media still relies on interpersonal promotion and without marketing strategies, plans and programs. This study aims to determine the planning and implementation of content management on Arswama Media's Instagram account. This research uses qualitative descriptive method. By the method of taking tricoagulation data collection. With the collection of data, the study produced Instagram content. Making insights from Arswama Media's Instagram account increase.